GENDER DALAM TINJAUAN TAFSIR - Zaitunah Subhan (Universitas Islam Negeri Imam Bonjol Padang, 2012)
The justice gender of issues continues to be voiced. The justice is the most central ideas as well as the highest goal is preached by every religion. Principal of mission of the al Qur’an Islamic Holy Book was revealed to free mankind from all forms of discrimination and oppression. Interpretations is the key to unlock the beauty of meaning which savings in the Qur'an.Keywords : Gender, Tafsir PerspectiveCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i1.34